Rural sociology - Doshi, S. L. (Shambhu Lal); Jain, Prakash Chandra, 1958- (Jaipur : Rawat Publications, 1999)
With reference to India.
Includes bibliographical references and index.
Keywords: Sociology, Rural. -- India; Sociology, Rural